2006
DOI: 10.1007/s11274-006-9268-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Saccharomyces cerevisiae strains on wine total antioxidant capacity evaluated by photochemiluminescence

Abstract: A preliminary investigation on 20 Aglianico del Vulture commercial wines from the Basilicata region proved the existence of a significant variability in total antioxidant capacity which can exert a potential impact on wine quality. Nineteen Saccharomyces cerevisiae strains were tested in Aglianico del Vulture on pilot scale fermentation and the experimental wines obtained were evaluated for the antioxidant capacity, ethanol and total polyphenols. At the ninth day of fermentation the experimental wines had an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 15 publications
1
14
0
2
Order By: Relevance
“…The total phenolic content of the wine samples varied from 1447 mg L −1 GAE in Merlot wines to 2912 mg L −1 GAE in Cabernet Sauvignon wines 25. It was clearly stated that ethanol fermentation with yeast increased the total antioxidant activity 26. In our study, total phenolic content of traditional and industrial vinegar values were 2690 mg L −1 and 2461 mg L −1 GAE, respectively ( P > 0.05).…”
Section: Resultsmentioning
confidence: 40%
“…The total phenolic content of the wine samples varied from 1447 mg L −1 GAE in Merlot wines to 2912 mg L −1 GAE in Cabernet Sauvignon wines 25. It was clearly stated that ethanol fermentation with yeast increased the total antioxidant activity 26. In our study, total phenolic content of traditional and industrial vinegar values were 2690 mg L −1 and 2461 mg L −1 GAE, respectively ( P > 0.05).…”
Section: Resultsmentioning
confidence: 40%
“…Tufariello et al (2014) provided evidence of a relationship between the yeast culture used in the winemaking process and the chemical profile of the wine, highlighting that the strain-specific properties of a yeast are able to change the colour and the aromatic profile of the final wine. A largescale analysis was carried out by analysing the effects of 19 different S. cerevisiae starter strains on the total polyphenol content and the antioxidant capacity of the resultant wines (Brandolini et al, 2007). The authors showed that the two parameters were different in each of the obtained wines, thus indicating that polyphenol extraction during vinification is a yeast strain-dependent feature.…”
Section: Functional Quality: Microbial Influence On Functional Propermentioning
confidence: 99%
“…It must be underlined that the strain of S. cerevisiae in inoculated fermentation exerts not only a prominent role on wine organoleptic quality, by transforming aromatic precursors of the grape must and by producing ex-novo aromatic substances, but it also influences polyphenol content, with a potential improvement of the healthy quality of wine (Brandolini et al 2007). In order to evaluate the effect of S. cerevisiae strain on the final content of these substances in wine, the 24 experimental wines of the two varieties were analysed for the content of total polyphenols (TPP) and the data were correlated with two other technological parameters, strain fermentative power (FP) and ethanol yield (ETOH).…”
Section: Influence Of S Cerevisiae Strain On Polyphenol Contentmentioning
confidence: 99%